Thoracic Endometriosis: A Presentation of an Uncommon Disease in a Black African Woman - John Omotola Ogunkoya; Taiwo Olufemi Solaja; Akinwale Folarin Ogunlade; Marion Itohan Ogunmola (Case Reports in Medicine)
Introduction. Endometriosis is defined as a chronic gynecologic disease which is characterized by the presence of endometrial glands and stroma in anatomical sites and organs outside the uterine cavity. The exact prevalence of endometriosis is difficult to determine because many women remain asymptomatic. However, endometriosis affects about 10% to 15% of women. Thoracic endometriosis (TES) is the most common endometriosis outside the abdominopelvic cavity. It refers to endometriosis within the thoracic cavity including the lung parenchyma, diaphragm, and pleural surfaces. It can manifest as catamenial chest pain, pneumothorax, hemoptysis, hemothorax, catamenial haemoptysis, and pulmonary nodules. Case Summary. A 39-years-old married female presented with recurrent right-sided chest pain of 22 years duration, recurrent cough of more than 20 years and progressive breathlessness of a month duration. The chest pain is pleuritic, and it often starts few days to the onset of her menses and lasts throughout menstrual flow only to abate after the stoppage of menstrual bleeding. Cough was unproductive, paroxysmal often worse with worsening chest pain. It disappears after the end of menstrual bleed. Breathlessness was initially on mild to moderate exertion before progressing to occasional breathlessness at rest. No history of orthopnea, paroxysmal nocturnal dyspnea, and pedal swelling was found. Over the years, she had presented to several clinics where she was said to have menstrual pain referred to the chest. Conclusion. Diagnosis of extrapelvic endometriosis can be challenging and delayed because it presents in a myriad of ways and in some cases, it may be difficult to link symptoms and the menstrual cycle.